Atypical Climacteric and Functional Ethylene Metabolism and Signaling During Fruit Ripening in Blueberry (Vaccinium sp.) - Wang, Yi-Wen; Acharya, Tej P.; Malladi, Anish; Tsai, Hsuan-Ju; NeSmith, D. Scott; Doyle, John W.; Nambeesan, Savithri U. (Frontiers in Plant Science, 2022)
Climacteric fruits display an increase in respiration and ethylene production during the onset of ripening, while such changes are minimal in non-climacteric fruits. Ethylene is a primary regulator of ripening in climacteric fruits. The ripening behavior and role of ethylene in blueberry (Vaccinium sp.) ripening is controversial. This work aimed to clarify the fruit ripening behavior and the associated role of ethylene in blueberry. Southern highbush (Vaccinium corymbosum hybrids) and rabbiteye (Vaccinium ashei) blueberry displayed an increase in the rate of respiration and ethylene evolution, both reaching a maxima around the Pink and Ripe stages of fruit development, consistent with climacteric fruit ripening behavior. Increase in ethylene evolution was associated with increases in transcript abundance of its biosynthesis genes, AMINOCYCLOPROPANE CARBOXYLATE (ACC) SYNTHASE1 (ACS1) and ACC OXIDASE2 (ACO2), implicating them in developmental ethylene production during ripening. Blueberry fruit did not display autocatalytic system 2 ethylene during ripening as ACS transcript abundance and ACC concentration were not enhanced upon treatment with an ethylene-releasing compound (ethephon). However, ACO transcript abundance was enhanced in response to ethephon, suggesting that ACO was not rate-limiting. Transcript abundance of multiple genes associated with ethylene signal transduction was upregulated concomitant with developmental increase in ethylene evolution, and in response to exogenous ethylene. As these changes require ethylene signal transduction, fruit ripening in blueberry appears to involve functional ethylene signaling. Together, these data indicate that blueberry fruit display atypical climacteric ripening, characterized by a respiratory climacteric, developmentally regulated but non-autocatalytic increase in ethylene evolution, and functional ethylene signaling.